Filamin A is required for somatostatin receptor type 5 expression and pasireotide-mediated signaling in pituitary corticotroph tumor cells. (15th March 2021) - Treppiedi, Donatella; Di Muro, Genesio; Mangili, Federica; Catalano, Rosa; Giardino, Elena; Barbieri, Anna Maria; Locatelli, Marco; Arosio, Maura; Spada, Anna; Peverelli, Erika; Mantovani, Giovanna
Abstract: Somatostatin receptor type 5 (SST5) represents the main pharmacological target in the treatment of adrenocorticotroph hormone (ACTH)-secreting tumors. However, molecular predictors of responsiveness to pasireotide require further investigation. The cytoskeleton protein filamin A (FLNA) modulates the responsiveness to somatostatin analogs (SSA) treatment in other types of pituitary tumors by regulating somatostatin receptor type 2 (SST2)/dopamine receptor type 2 (DRD2) expression and activity. Here, we aimed to test the involvement of FLNA in the modulation of SST5 response to SSA in human and murine tumor corticotrophs. Western blot analysis of human corticotropinomas showed that FLNA and SST5 correlate. Both in human primary cultures and AtT-20 cells, FLNA genetic silencing caused a decrease of receptor expression level. Moreover, pasireotide-mediated SST5 downregulation observed in AtT-20 control cells was no further detected in FLNA silenced cells. In AtT-20 cells, in situ PLA experiments revealed an increased number of SST5-FLNA complexes following pasireotide incubation. Finally, FLNA knock down abolished pasireotide-induced SST5 actions on hormone secretion, cell proliferation and apoptosis. In conclusion, FLNA is implicated in SST5 expression modulation and signaling. Highlights: SST5 and FLNA protein levels correlate in human ACTH-secreting pituitary tumors. Pasireotide binding to SST5 promotes the formation of SST5-FLNA complexes. FLNA knockdown abolishes pasireotide-induced SST5 signaling in tumoral corticotrophs.